2017
DOI: 10.1007/s13337-017-0402-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of hand, foot and mouth disease in Daklak Province, Vietnam and associated factors of severe cases

Abstract: The Hand, Foot and Mouth Disease (HFMD) outbreaks occurred throughout Daklak province, Vietnam in 2011. This study reviewed all 744 medical records of HFMD patients admitted to Daklak Hospital in 2011 to describe the clinical characteristics of HFMD patients and determined factors associated with severe illness. Among 744 patients, 63 (8.5%) cases were severe. Most (695, 93.4%) of the cases were 3 years old or younger, and 464 (62.4%) were boys. The number of cases peaked between August and November. Most (726… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 13 publications
6
19
0
2
Order By: Relevance
“…It has been reported that the mortality of severe HFMD was as high as 3.0% from 2008 to 2012 in China mainland [7]. Although the inactivated EV71 vaccine has been widely used to vaccinate infants and young children in several provinces of mainland China and has shown to be effective at protecting them from EV71-associated severe HFMD, the number of severe cases is still large, posing a threat to infants and young children in rural areas of Asia-Pacific region [46, 8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the mortality of severe HFMD was as high as 3.0% from 2008 to 2012 in China mainland [7]. Although the inactivated EV71 vaccine has been widely used to vaccinate infants and young children in several provinces of mainland China and has shown to be effective at protecting them from EV71-associated severe HFMD, the number of severe cases is still large, posing a threat to infants and young children in rural areas of Asia-Pacific region [46, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Так же как и в Хошимине, средний возраст пациентов составил 20 месяцев, 93,4% случаев пришлось на группу детей до 3 лет. Энтеровирус EV-А71 был выявлен у 63% «тяжелых» пациентов с положительным результатом тестирования на ЭВ [35]. Заболеваемость и смертельные случаи, связанные с HFMD, в 2011 г. регистрировались во всех частях Вьетнама, однако наибольшая доля как заболевших, так и умерших пришлась на южные провинции; в 2012 г. эпидемия распространилась на северную часть.…”
Section: заболеваемость энтеровирусной инфекцией в социалистической рunclassified
“…Наибольшее число тяжелых форм ЭВИ и летальных исходов во Вьетнаме было связано с вирусом EV-A71 [15,16,21,35]. В 2011 г. инфекция, обусловленная EV-A71, была лабораторно под-тверждена в 82% случаев ЭВИ, закончившихся летальным исходом [21].…”
Section: этиологические агенты энтеровирусной инфекции во вьетнамеunclassified
“…Although this viral infection remains largely contagious 4, 5 , it is self-limiting and benign. Severe cases reportedly occurs in lower incidences (3.2% to 8.5%) and fatalities are rare 68 . Starting in the West during the mid-1970’s 1, 2 HFMD emerged in the Asia-Pacific region in mid-1990s 9– 11 heralding as a major public health hazards 2, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…With the complaints of mild-to-moderate fever (≥38.5°C 8 ; 101.3°F) childhood HFMD, characteristically manifest with body rashes 1, 4 , mostly of the knees and buttocks 4, 14 , augmented by painful oral/buccal ulcers and blisters. Papulo-vesicular rash in the extremities consequently forms pustules 6 .…”
Section: Introductionmentioning
confidence: 99%